1979
DOI: 10.1093/ajcn/32.5.1033
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of oxidation derivatives of cholesterol on cultured aortic smooth muscle cells and their effect on cholesterol biosynthesis

Abstract: Aortic smooth muscle cell death is an important initial lesion of atherosclerosis. A number of autooxidation products of cholesterol which has been recognized recently has the capability of inducing rabbits' aortic smooth cell death in vitro. Twelve oxidation derivatives of cholesterol, available commercially, were dissolved in small amounts of ethanol, then added to the culture medium at levels not exceeding 0.8%. The medium contained 10% fetal calf's serum which served as an in situ vehicle for the sterols. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
61
1
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(69 citation statements)
references
References 20 publications
5
61
1
2
Order By: Relevance
“…[11][12][13][14][15][16] Because cholesterol oxides (ChOx) have been ubiquitously identified in human plasma and atheromatous lesions, their involvement in the atherogenic process is receiving increasing scrutiny. [17][18][19][20][21] ChOx may influence the atherogenic process in several ways, since they are cytotoxic toward the cellular components of the arterial wall, [22][23][24] increase vascular permeability, 25 promote cholesterol ester formation and accumulation, 26 -28 inhibit prostaglandin I 2 synthesis by endothelial cells, 29 and perturb cholesterol biosynthesis. 30,31 Previously, we and others have shown that cholesterol feeding of New Zealand White rabbits leads to increased plasma and aortic wall cholesterol oxide content, 7,32 which is reduced with the antioxidant agent probucol.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16] Because cholesterol oxides (ChOx) have been ubiquitously identified in human plasma and atheromatous lesions, their involvement in the atherogenic process is receiving increasing scrutiny. [17][18][19][20][21] ChOx may influence the atherogenic process in several ways, since they are cytotoxic toward the cellular components of the arterial wall, [22][23][24] increase vascular permeability, 25 promote cholesterol ester formation and accumulation, 26 -28 inhibit prostaglandin I 2 synthesis by endothelial cells, 29 and perturb cholesterol biosynthesis. 30,31 Previously, we and others have shown that cholesterol feeding of New Zealand White rabbits leads to increased plasma and aortic wall cholesterol oxide content, 7,32 which is reduced with the antioxidant agent probucol.…”
mentioning
confidence: 99%
“…An excessive amount of cholesterol oxides damages endothelial cells [8,9], smooth muscle cells [2,10], and fibroblasts [11,12], and accumulating evidence suggests that cholesterol oxides are toxic to neural cells in nerve growth factor-differentiated neuronal PC12 cells as a model for sympathetic neurons [13,14], cultured cerebellar granule cells [1], and microglial cells [15]. Although the molecular mechanisms by which cholesterol…”
Section: Introductionmentioning
confidence: 99%
“…They are also reported to be present at relatively high concentrations in atherosclerotic plaques (4), and contribute to the development of atherosclerosis (5)(6)(7)(8)(9). We have reported that 7-ketocholesterol (7-KCHO), an oxysterol, induced the apoptosis and inhibited the migration (13) of human smooth muscle cells (SMC) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%